PENGARUH SISTEM REMUNERASI, KETERLIBATAN KERJA, DAN SPIRITUALITAS DI TEMPAT KERJA TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN PT LAUT TIMUR ARDIPRIMA SAMARINDA - SANDY LUKMANA; YONHATAN PONGTULURAN; GUSTI NOORLITARIA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this research was to verify the effect of Remuneration System, Work Involvement, and Spirituality at Work toward Organizational Commitment of PT Laut Timur Ardiprima Samarinda employee. To collected the data this research, researcher used purposive sampling method. The sample which used in this research was 60 respondents with the criteria of employee who has been worked in PT Laut Timur Ardiprima Samarinda employee Samarinda at last two year. This research used mulitple linear regression analysis with SPSS as an instrument to calculate the data. The result showed that there was a positive effect and significant between remuneration system toward organizational commitment. And there was a positive effect and significant between work involvement toward organizational commitment. And there was also a positive effect and significant between spirituality at work toward organizational commitment.Keywords : remuneration system, work involvement, spirituality at work, organizational commitment